Detection of busulfan adducts on proteins. (20th October 2016) - Acosta‐Martin, Adelina E.; Antinori, Paola; Uppugunduri, Chakradhara Rao S.; Daali, Youssef; Ansari, Marc; Scherl, Alexander; Müller, Markus; Lescuyer, Pierre
Abstract : Rationale: Busulfan is a bifunctional alkyl sulfonate antineoplastic drug. This alkylating agent was described as forming covalent adducts on proteins. However, only limited data are available regarding the interaction of busulfan with proteins. Mass spectrometry and bioinformatics were used to identify busulfan adducts on human serum albumin and hemoglobin. Methods: Albumin and hemoglobin were incubated with busulfan or control compounds, digested with trypsin and analyzed by liquid chromatography/tandem mass spectrometry (LC/MS/MS) on a Thermo Fisher LTQ Orbitrap Velos Pro. MS data were used to generate spectral libraries of non‐modified peptides and an open modification search was performed to identify potential adduct mass shifts and possible modification sites. Results were confirmed by a second database search including identified mass shifts and by visual inspection of annotated tandem mass spectra of adduct‐carrying peptides. Results: Five structures of busulfan adducts were detected and a chemical structure could be attributed to four of them. Two were primary adducts corresponding to busulfan monoalkylation and alkylation of two amino acid residues by a single busulfan molecule. Two others corresponded to secondary adducts generated during sample processing. Adducts were mainly detected on Asp, Glu, and His residues. These findings were confirmed by subsequent database searches and experiments with synthetic peptides. Conclusions: The combination of in vitro incubation of proteins with the drug of interest or control compounds, high‐resolution mass spectrometry, and open modification search allowed confirmation of the direct interaction of busulfan with proteins and characterization of the resulting adducts. Our results also showed that careful analysis of the data is required to detect experimental artifacts. Copyright © 2016 John Wiley & Sons, Ltd.